Półka literacka 2009 - Agnieszka Nęcka (Postscriptum Polonistyczne)
The author analyzes the situation in the field of publishing Polish belles lettres in 2009. She selects ten books that in her opinion represent the most interesting achievements in prose and poetry. Books that are discussed in the article have been written by the authors representing different generations: Andrzej Bart (Rewers), Joanna Bator (Piaskowa Góra), Zbigniew Kruszyński (Ostatni raport), Janusz Rudnicki (Śmierć czeskiego psa), Andrzej Stasiuk (Taksim), Olga Tokarczuk (Prowadź swój pług przez kości umarłych), Bartosz Konstrat (Samochody i krew), Tadeusz Pióro (Abecadło), Piotr Sommer (Dni i noce), Piotr Szewc (Moje zdanie).